Nilai-nilai Pendidikan Akhlak pada Film Animasi Hafiz dan Hafizah dalam Membentuk Karakter Anak yang Cerdas dan Saleh - Firsya, Rahmatul Hasni; Wiza, Rahmi (Lembaga Yasin AlSys, 2025)
This study examines the values of moral education in the animated film Hafiz and Hafizah in shaping intelligent and pious children's character. The purpose of this research is to identify the moral education values present in the animated film. The method used is a qualitative approach with content analysis as the research type. The subjects of the study consist of two video samples taken from the YouTube channel Hafiz and Hafizah, titled “Apa Yang Disukai Allah Part 2” and “Bazzar Untuk Kebaikan Part 2.” The data collection instruments included observation and documentation. The results indicate that the moral education values in the animated film Hafiz and Hafizah encompass (1) moral education values to Allah in the context of being devout to Allah Swt and (2) moral education values to others in the context of sharing and forgiving one another. These findings provide significant contributions to the development of children's character through animated media and can serve as a reference for moral education in family and school environments.